Evaluation of Empirical Formulas to Estimate Axial Capacity of Bored Pile in West Java, Indonesia - Laura Naomi Roniar; Cevin Hartanto; Masyhur Irsyam; Yuamar Imarrazan Basarah; Tony Budianto Sihite (Himpunan Ahli Teknik Tanah Indonesia, 2023)
Pile foundation is part of the substructure that plays an important role in carrying and supporting the load acting on it. Therefore, a proper foundation design by estimating the bearing capacity of pile foundation is needed to ensure the safety of the building foundation. To achieve better estimation of pile capacity, analysis of the axial bearing capacity should be verified by pile test results such as Static Loading Test or dynamic test with a Pile Driving Analyzer. Based on the pile test data, the values of the skin friction and end bearing resistance can be back calculated, and hence it can be used in the calculation of pile bearing capacity using empirical methods. In this study, bearing capacity analysis was performed for drilled pile foundations, which had been tested using Static Loading Test and Pile Driving Analyzer. The analysis was carried out by comparing the results of empirical calculations for each test pile with the results of field tests. The calculation results were then compared to the empirical adhesion factor (alpha) method, which is commonly used by practicing engineers in Indonesia, according to the methods proposed by Kulhawy (1984), Reese & Wright (1977), and Reese & O'Neil (1988). Based on the 104 test piles data, the results are more in good agreement with the adhesion factor proposed by Kulhawy (1984) with a correlation of undrained shear strength, cu of 8 NSPT, a correlation of unit skin friction for sandy soils of 2.2 NSPT, and a correlation of unit end bearing for sandy soils of 70 NSPT-ave.